ANALYSIS OF GEOMAGNETIC FIELD ALONG SEISMIC PROFILE P4 OF THE INTERNATIONAL PROJECT POLONAISE'97 - Grabowska T.; Bojdys G. (My University, 2004)
This paper presents relative secular variations of the total intensity of the geomagnetic field against a background of results of magnetic anomaly interpretation along seismic profile P4. Profile P4 crosses a Variscan folding zone in the Paleozoic Platform (PLZ), the Trans-European Suture Zone (TESZ), and the Polish part of the East European Craton (EEC). Secular geomagnetic field variations |T→| measured in 1966–2000 along a line adjacent to seismic profile P4 were analysed. The study of secular variations, reduced to the base recordings at the Belsk Magnetic Observatory, showed that the growth of geomagnetic field at the East European Craton was slower than in the Trans-European Suture Zone and the Paleozoic Platform.A 2D crustal magnetic model was interpreted as a result of magnetic modelling, in which seismic, geological and geothermal data were also used. The modelling showed that there were significant differences in the magnetic model for geotectonic units, which had been earlier determined based on deep seismic survey data. It should be noted that a fundamental change of trend of the relative secular variations was observed at the slope of the Precambrian Platform. After analysing the geomagnetic field observed along profile P4, the hypothesis that the contact between Phanerozoic and Precambrian Europe lies in Poland's territory can be proven.
Keywords: Relative secular variations; Geomagnetic field; Magnetic modelling; Crustal magnetic model; PLZ; TESZ; EEC